2021
DOI: 10.1097/nnr.0000000000000550
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Involvement, Self-Efficacy, and Transition Readiness in Youth With Sickle Cell Disease

Abstract: Background: Transition to adult healthcare is a critical time for adolescents and young adults (AYAs) with sickle cell disease, and preparation for transition is important to reducing morbidity and mortality risks associated with transition.Objective: We explored the relationships between decision-making involvement, self-efficacy, healthcare responsibility, and overall transition readiness in AYAs with sickle cell disease prior to transition.Methods: This cross-sectional, correlational study was conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…However, this is the first study, to our knowledge, that examines the perspectives of AYA-SCD and their clinicians on the role of video games in optimizing the successful transition from pediatric to adult care. In addition, this study identified several key determinants to effective self-efficacy and SDM, which are key to AYA-SCD transition success and taking responsibility for their health care 36,37 . Understanding the role of SDM in AYA-SCD is essential in developing interventions that appropriately address the unique challenges that AYA-SCD face, particularly related to stigma and inablilty to engage due to disease complications like pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is the first study, to our knowledge, that examines the perspectives of AYA-SCD and their clinicians on the role of video games in optimizing the successful transition from pediatric to adult care. In addition, this study identified several key determinants to effective self-efficacy and SDM, which are key to AYA-SCD transition success and taking responsibility for their health care 36,37 . Understanding the role of SDM in AYA-SCD is essential in developing interventions that appropriately address the unique challenges that AYA-SCD face, particularly related to stigma and inablilty to engage due to disease complications like pain.…”
Section: Discussionmentioning
confidence: 99%
“…The transition from pediatric to adult care in children with chronic diseases is well-recognized as a critical window because it represents the intersection of normal adolescent development, change in health care access and increased clinical manifestations of disease 4–6 . Hallmarks of transition readiness among AYA-SCD include self-efficacy, that is, patients’ belief in their ability to manage their disease, active participation in shared decision-making (SDM), and adequate disease-specific knowledge 7–9 . However, there is limited data on core determinants of the successful engagement of AYA-SCD in decision-making.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The original study from which these data were collected used a convenience sample of AYA living with sickle cell disease and their family caregivers who were recruited from a large, comprehensive sickle cell disease clinic at an academic hospital in Washington, DC. There were 25 adolescents, 25 young adults and 50 family caregivers recruited for the original study (Varty et al, 2022). A power analysis was conducted for the original study, but it was not conducted for this secondary analysis due to the design.…”
Section: Introductionmentioning
confidence: 99%
“…The original study's purpose was to explore the relationships between decision‐making involvement, self‐efficacy, healthcare responsibility and overall transition readiness from both the perspective of the AYA living with sickle cell disease and their family caregiver (Varty et al, 2022). It was conducted between October 2019 and February 2020 and was guided by the Individual and Family Self‐Management Theory.…”
Section: Introductionmentioning
confidence: 99%